Marine & freshwater products handbook (Technomic Pub. Co, 2000)
This definitive reference is the most comprehensive handbook of information ever assembled on foods and other products from fresh and marine waters. Marine and Freshwater Products Handbook covers the acquisition, handling, biology, and the science and technology of the preservation and processing of fishery and marine products.